A comprehensive review of lenalidomide in B-cell non-Hodgkin lymphoma. (August 2016) - Arora, Mili; Gowda, Sonia; Tuscano, Joseph
Lenalidomide, an immunomodulatory drug that the US Food and Drug Administration (FDA) approved for the treatment of multiple myeloma, 5q- myelodysplasia and mantle-cell lymphoma (MCL), has encouraging efficacy in other B-cell malignancies. Its unique mechanism of action is in part due to altering the tumor microenvironment and potentiating the activity of T and natural-killer (NK) cells. Impressive clinical activity and excellent tolerability allows broad applicability. Lenalidomide has been used in a wide range of B-cell malignancies for years, but in 2013, the FDA marked its approval as a single agent only in relapsed/refractory mantle-cell lymphoma. Perhaps most impressive is the efficacy of lenalidomide when combined with monoclonal antibodies. Impressive efficacy and toxicity profiles with the combination of lenalidomide and rituximab in B-cell lymphomas in both the upfront and relapsed/refractory setting may allow a shift in our current treatment paradigm in both indolent and aggressive non-Hodgkin lymphoma (NHL). This review will summarize the current data in the relapsed/refractory and front-line setting of NHL with single-agent lenalidomide as well as its use in combination with other agents.